Keyboard Traditions in French music art in first half of 20 Century: communicative aspect - Zhukova, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
Article is devoted to the questions of preservation and interpretation of the French keyboard traditions, which appear here as a peculiar communicative code, clear both to the composer and performer. Relevance of the study is in the fact that musical text in the score, which should not be considered as complete guideline for the performer’s interpretation, requires additional explanations for “decoding”. The commitment of the detailed instructions reaches a quite high degree in French keyboard music. The performer’s interpretation requires the knowledge not only of symbols themselves, but also of historical context, of literary and scientific sources. In the Ukrainian musicology this area is still not enough investigated. Thus, the main objective of the study can be considered as the compensation of blanks in the studying the French musical traditions at the example of the keyboard music of the different periods of the French music history, the involving the foreign sources to the field of research; involving the experience of the foreign colleagues to the educational and creative process. During the research the theoretical and empirical methods were applied: the studying of the musical and theoretical literature, the experience of the foreign colleagues in the master-classes format, the analysis of the music pieces. The Results of research were received during the studying the literature and music pieces, the analysis and the summarizing of the information, masterclasses with the European musicians, the author’s own work at the pieces, the teaching work. Due to that it was possible to accumulate a significant experience in the questions of the interpretation for the transmitting to a new generation of the performers and scholars. The study was done following the experience received not only from the documentary fixed information, but also from the other, often verbal or unevident sources, which substantially enriches the common picture. In such a manner, the conclusions allow to consider the French keyboard traditions as the unique carrier of the valuable information for the performer and the scholar, which helps to understand keyboard music of French authors deeper, than the clear music score suggest — and, respectively, having a specific communicative potential. The study’s significance for the science, art and education lies in the active development of the problems of the correct interpretation of the keyboard music by French composers is capable to raise substantially the level of performer’s understanding and the scientific thinking of this music, its national specific features, enriching thereby the palette of the keyboard repertoire.